Pop Princess - Cohn, Rachel (New York : Simon & Schuster Books for Young Readers, 2004)
Yearning to escape the small Massachusetts town where her family retreated after her sister's death, Wonder Blake gets her chance when her sister's manager offers Wonder a record contract on her sixteenth birthday.
Keywords: Singers -- Fiction; Music trade -- Fiction; Popular music -- Fiction; Family problems -- Fiction; Interpersonal relations -- Fiction; Massachusetts -- Fiction